Data Hiding in Digital Images by using DOM Steganographic Technique - Kumar, Divyank; Kumar, Arun; Barnawl, Ankita; Dubey, Shivani (International Journal of Computer Sciences and Engineering, 2025)
Since the rise of the internet, one of the most important factors of information technology and communication has been the security of information. Now a day, mostly business organizations face the problem in sharing their confidential documents. This project is developed for hiding file (secret message, document) in any image by using Steganography. Many different carrier file formats can be used, but digital images are the most popular because of their frequency on the internet. In this paper, we are proposing a method of encrypting the text files in an image in order to text the accuracy and efficiency of encryption. This process helps to send the information to the authorised party without any potential risk. The proposed method will help to secure the content within the image and will help to make the document much securer because even though if an unauthorised person succeeds in being able to hack the image, the person will not able to read the message.